Microstructural aspects of additive manufacturing of AlLi alloys with high Li content - Dongmei Liu; Burak Yürekli; Tobias Ullsperger; Gabor Matthäus; Lisa Schade; Stefan Nolte; Markus Rettenmayr (Materials & Design, 2021)
Laser assisted powder bed fusion using a binary AlLi alloy with high Li content (Al–14 at.%Li) has been performed for the first time. The aim was to generate microstructures with extended concentration range of AlLi alloys in which the formation of the brittle δ–AlLi phase is avoided. From conventional casting processes it is known that the δ–AlLi phase is detrimental to mechanical properties and corrosion resistance. All processing steps from the production of ingots free of contamination, oxidation and macrosegregation to the synthesis of fine spherical powders appropriate for additive manufacturing to the powder bed fusion routine using ultra short pulses have been investigated. In comparison with as–cast microstructures, the fast cooling rate after laser assisted powder bed fusion leads to a uniform Li distribution in the primary α phase rather than to the formation of δ–AlLi, contributing to comparably high hardness of the samples.